Comparison of Dermatology Life Quality Index Scores in Adults and Adolescents with Alopecia Areata - Kent A. Hanson; Sergio Vañó-Galván; Andrew Messenger; Helen Tran; Lynne Napatalung; Keith L. Davis; Lizzi Esterberg; Ernest H. Law (Dermatology and Therapy)
Abstract Introduction This study assessed Dermatology Life Quality Index (DLQI) scores of patients with alopecia areata (AA) and compared scores between adults and adolescents. Methods This was a retrospective chart review in France, Germany, Spain, and the UK. Patients with ≥ 50% scalp hair loss (SHL) due to AA and a DLQI score recorded at their index date (first date of ≥ 50% SHL) were included. The DLQI (scale 0–30; higher scores indicate greater impact) assesses the impact of AA on health-related quality of life (QOL). Multivariable linear regression was used to examine the effect of age on DLQI score, adjusting for covariates. Modified Poisson regression analysis was used to estimate relative risks (RRs) between age groups and DLQI categories (none to moderate effect, very large effect, and extremely large effect), adjusting for covariates, including baseline Severity of Alopecia Tool (SALT) score. Results Overall, 335 patients were included (249 adults, 86 adolescents). At index, adults had a higher mean (SD) SALT score than adolescents (63.7 [15.5] vs 60.4 [12.8]), whereas mean (SD) DLQI scores were higher in adolescents than adults (22.1 [5.3] vs 18.2 [7.5]). Most patients (84%) had DLQI scores indicating a very large or extremely large impact on their lives; this was more pronounced in adolescents than adults (98% vs 80%). In the multilinear model, adolescents had significantly higher DLQI scores than adults (β = 3.51; P < 0.001), indicating a 3.51-point increase in DLQI score associated with being an adolescent. The RR (95% CI) of a DLQI score indicating a very large effect (1.28 [1.07–1.53]) or extremely large effect (1.40 [1.21–1.61]) relative to no or moderate effect was significantly higher for adolescents vs adults. Conclusion This study demonstrates that, at the time of experiencing ≥ 50% SHL due to AA, both adults and adolescents reported significant impacts on their QOL, with a higher impact on adolescents.